2021
DOI: 10.1530/ec-20-0552
|View full text |Cite
|
Sign up to set email alerts
|

Free testosterone and cardiometabolic parameters in men: comparison of algorithms

Abstract: Objective. Calculating the free testosterone level has gained increasing interest and different indirect algorithms have been suggested. The objective was to compare free androgen index (FAI), free testosterone estimated using the linear binding model (Vermeulen: cFTV) and the binding framework accounting for allosterically coupled SHBG monomers (Zakharov: cFTZ) in relation to cardiometabolic conditions. Design. A prospective cohort study including 5,350 men, aged 30-70 years, participating in population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In our study, by applying the standard threshold of plasma LH levels (9.4 IU/L), we found that serum FSH equal to 8 IU/L could reinforce clinical decisions in distinguishing primary and secondary OrH. This finding is supported by a few data currently available in the literature suggesting that a confirmed plasma FSH > 8 IU/L is usually associated with irreversible testicular damage, hence defining primary hypogonadism [ 44 48 ]. In fact, the Italian Agency for Drug Administration allows the reimbursement of FSH replacement therapy only in men with idiopathic impaired spermatogenesis having confirmed serum FSH levels less than 8 IU/L ( http://www.agenziafarmaco.gov.it/ ).…”
Section: Discussionsupporting
confidence: 74%
“…In our study, by applying the standard threshold of plasma LH levels (9.4 IU/L), we found that serum FSH equal to 8 IU/L could reinforce clinical decisions in distinguishing primary and secondary OrH. This finding is supported by a few data currently available in the literature suggesting that a confirmed plasma FSH > 8 IU/L is usually associated with irreversible testicular damage, hence defining primary hypogonadism [ 44 48 ]. In fact, the Italian Agency for Drug Administration allows the reimbursement of FSH replacement therapy only in men with idiopathic impaired spermatogenesis having confirmed serum FSH levels less than 8 IU/L ( http://www.agenziafarmaco.gov.it/ ).…”
Section: Discussionsupporting
confidence: 74%
“…As no previous study in cluster headache has been done with the same methodology of measuring testosterone, the power calculation was done with data from healthy persons. The expected mean fT was 434.5 (SD: 163.8) pmol/L in the control group based on previous findings 27 . With 60 in each group and the assumption of an equal SD in the cluster headache group, an alpha of 0.05 and a power of 0.8 enables the study a power to detect a reduction of 10%.…”
Section: Methodsmentioning
confidence: 67%
“…The expected mean fT was 434.5 (SD: 163.8) pmol/L in the control group based on previous findings. 27 With 60 in each group and the assumption of an equal SD in the cluster headache group, an alpha of 0.05 and a power of 0.8 enables the study a power to detect a reduction of 10%. Therefore, the number of participants in each group was determined to be 60.…”
Section: Study Sizementioning
confidence: 99%
“…A unitless free androgen index (FAI) was generated by dividing baseline total testosterone concentrations (nmol/L) by SHBG concentrations (nmol/L) and multiplying by a factor of 100. 17 Similarly, a unitless free estradiol index (FEI) was generated by dividing baseline estradiol concentrations (nmol/L; converted from pmol/L) by SHBG concentrations (nmol/L) and multiplying by a factor of 100 000. [18][19][20][21] The free testosterone index (FTI) incorporated information on total testosterone, SHBG, and albumin and was calculated and validated as described.…”
Section: Measurement Of Serum Sex Hormone Concentrationsmentioning
confidence: 99%